2019
DOI: 10.2494/photopolymer.32.705
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of UV-LED Photopolymerisation over Conventional UV-Mercury for Polyurethane Acrylate Coating

Abstract: This paper presents the effect of UV-LED and UV-mercury as the light source toward curing behaviour of urethane acrylate coating. The UV-curable coating was prepared based on aliphatic urethane acrylate oligomer, 2-ethylhexyl acrylate (2-EHA), methyl methacrylate (MMA), trimethylolpropane triacrylate (TMPTA), and commercial photoinitiator. The effect of irradiation time on curing behaviour was investigated using Fourier Transform Infra-Red (FTIR) and the percentage of C=C conversion was calculated. From the AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…In our recent paper, the effects of UV-LED irradiation time towards curing behaviour of urethane acrylate coating was investigated. We had successfully demonstrated that the properties of coating using UV-LED was superior to the conventional UV-mercury lamp at a faster curing rate [ 40 ]. Following this, the effect of fluorinated monomer content to obtain a hydrophobic coating by utilising UV-LED technology was further explored.…”
Section: Introductionmentioning
confidence: 99%
“…In our recent paper, the effects of UV-LED irradiation time towards curing behaviour of urethane acrylate coating was investigated. We had successfully demonstrated that the properties of coating using UV-LED was superior to the conventional UV-mercury lamp at a faster curing rate [ 40 ]. Following this, the effect of fluorinated monomer content to obtain a hydrophobic coating by utilising UV-LED technology was further explored.…”
Section: Introductionmentioning
confidence: 99%
“…This last characteristic becomes even more critical when LEDs are used as UV irradiation sources. 26 Practically speaking, it also provides excellent spatial or temporal control, allowing the polymerization process as well as the properties/compositions of the polymeric product to be controlled. 27–49 Moreover, photopolymerization frequently offers a rapid cure, allowing for quick processing and lower costs.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the reactions are usually performed at room temperature thus reducing any energetic cost associated with heating and cooling cycles. This last feature is even more relevant when LEDs are employed as UV irradiation sources in place of regular Hg-Xe lamps [17]. On practical aspects, the polymerization can be controlled both temporally Abbreviations: AFTC, addition fragmentation chain transfer; AIBN, azobisisobutyronitrile; Bis-GMA, bisphenol A diglycidyl dimethacrylate; BMDG, bis(4-methoXybenzoyl)diethylgermane; BMDO, 56-benzo-2-methylene-1,3-dioXepane; BMSOC, bis-methylene-spiro-orthocarbonate; ε-CL, ε-caprolactone; CAS, cyclic allylic sulphide; CiO-α-CD, cinnamoyl modified-α-cyclodextrine; CLIP, continuous liquid interface production; COD, cyclooctodiene; COE, cyclooctene; CP, cyclopentene; CQ, camphorquinone; CR • , cyclobutane radicals; CROP, cationic ring-opening polymerization; CVA, cyclic vinyl acetal; DBN, 15-diazabicyclo[4.3.0]non-5ene; DBU, 1,8-diazabicyclo(5.4.0)undec-7-ene; DCPD, dicyclopentadiene; DLP, digital light processing; EDMAB, ethyl 4-(dimethylamino)benzoate; FRPCP, freeradical promoted cationic polymerization; IMes, 1,3-bis(mesityl)imidazol-2-ylidene; ITX, isopropopylthioXanthone; LED, light-emitting diode; L-LA, L-lactide; MDO, 2methylene-1, 3-dioXolane; MFROMP, metal-free ring-opening metathesis polymerization; NB, norbornene; NCA, N-carboXyanhydride; NHC, N-heterocyclic car-bene; NIPAAm, N-isopropylacrylamide; N-IR, near infra-red; PAG, photoacid generator; PBG, photobase generator; PBZ, poly(benzoXazine); PC, photocatalyst; PCL, Poly(εcaprolactone); PCLDMA, poly(caprolactone dimethacrylate); PCOE, poly(cyclooctene); PCP, poly(cyclopentene); PDCPD, poly(dicyclopentadiene); PEG, polyethyleneglycol; PEG-PGA-DA, poly(ethylene glycol-co-glycolic acid) diacrylate; PET-RAFT, photoinduced electron transfer-reversible addition fragmentation transfer; PI, photoinitiator; PLA, poly(lactide); PMA, poly(methyl acrylate); PMMA, poly(methyl methacrylate); PNB, poly(norbornene); POX, polyoXazoline; PPG, poly(propylene glycol); PS, photosensitizer; PSRu, photoswitchable ruthenium catalyst; PVL, poly(δ-valerolactone); RICFP, radical induced cationic frontal polymerization; ROP, ring-opening polymerization; ROMP, ring-opening metathesis polymerization; RROP, radical ring-opening polymerization; RTI, radical thermal initiator; SIMes, 1,3-bis(mesityl)-4,5-dihydroimidazol-2-ylidene; SLA, stereolithography; SOC, spiro-ortho carbonate; SOE, spiro-ortho ester; TBD, 1,5,7-triaza-bicylo [4,4,0]undec-5-ene; t-BuP1, tert-butylimino-tris(dimethylamino)phosphorene; THF, tetrahydrofuran; TMC, trimethylene carbonate; TMG, 1,1,3,3-tetramethylguanidine; TPPT, 2,4,6-triphenylpyrylium tetrafluoroborate; UCNP, up-conversion nanoparticle; UV, ultra-violet; δ-VL, δ-valerolactone; VCP, vinylcyclopropane.…”
Section: Introductionmentioning
confidence: 99%